A bibliometric of research trends in acupuncture for spinal cord injury: Quantitative and qualitative analyses - Huang, Yi; He, Kelin; Fang, Dandan; Ni, Fengjia; Qiu, Bei; Liang, Kang; Ma, Ruijie (Frontiers in Neurology, 2022)
Abstract Introduction: Spinal cord injury (SCI) is a severe disease of the central nervous system with a very high disability rate that seriously affects the daily life of patients. Acupuncture is one of the rehabilitation therapies that has shown significant efficacy in treating post-SCI complications such as motor disorders, neuropathic pain, and neurogenic bladder. Current studies have focused on the effectiveness and mechanisms of acupuncture for SCI, but no studies are available to analyze the bibliometrics of publications related to this area. Methods: Publications related to acupuncture for SCI were retrieved from the Web of Science Core Collection for quantitative and qualitative analyses. The quantitative analysis was unfolded in the following six main areas: annual publications, countries, institutions, authors, sources, and keywords. The qualitative analysis section screened out publications with high annual citation rates and categorized them according to the study content. Results: There were 213 relevant publications, more than half of which were journal articles. The number of publications showed a fluctuating upward trend. China and the United States were hub countries for related publications and had extensive cooperation with other countries. The most relevant author was Yuanshan Zeng from Sun Yat-sen University, China. The efficacy and mechanism of acupuncture for neuropathic pain after SCI was the first research hotspot in this field, and electroacupuncture was the most widely used technique. In the past five years, the mechanism of acupuncture to improve the local microenvironment of SCI and promote nerve regeneration had become a new research trend. At the same time, acupuncture had been gradually applied to various complications after SCI and in veterinary medicine. Conclusion: The findings suggest that research on acupuncture for SCI is still flourishing, and more research on electroacupuncture for promoting nerve repair and regeneration after SCI will be available in the future.